2019
DOI: 10.1055/s-0037-1611545
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Regioselective Bromination of Electron-Rich Aromatic Rings Using n Bu4NBr

Abstract: Electrochemical regioselective bromination of electron-rich aromatic rings using stoichiometric tetrabutylammonium bromide ( n Bu4NBr) has been accomplished under mild conditions. This protocol provides an environmentally friendly and simple way for the construction of C–Br bond in moderate to high yields with wide functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Based on the above experimental results and previous reports, a plausible reaction mechanism was proposed in Scheme . First, bromine anion was oxidized to the bromine radical at the anode.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Based on the above experimental results and previous reports, a plausible reaction mechanism was proposed in Scheme . First, bromine anion was oxidized to the bromine radical at the anode.…”
mentioning
confidence: 73%
“…In the past decades, electrochemical organic synthesis has witnessed significant progress because one can use clean electricity as the surrogate for the external oxidants, which remarkably eliminated the environmental pollution issues . Therefore, we wish to describe our newly developed electrochemical bromination protocol for the 2-aminopyridines under catalyst- and oxidant-free conditions at room temperature …”
mentioning
confidence: 99%
“…In recent years, electrochemical bromination of arenes has been developed. For example, Thasan and Kumarasamy, Fachigami et al, and Lei et al, and others reported electrochemical bromination of aromatic compounds . In 2018, our group reported copper-catalyzed electrochemical C–H amination of arenes with secondary amines, which proceeded via a single-electron-transfer (SET) process .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these indole compounds can be achieved by the electrophilic C–H bromination of indoles with different brominating reagents (Scheme 1a). 5 In addition, the intramolecular annulation/bromination of o -alkynylanilines or o -alkynylarylazides has also proved to be an efficient route to 3-bromoindole derivatives (Scheme 1b). 6 Despite considerable progress that has been achieved, most approaches suffer from some limitations, such as the employment of poisonous and corrosive brominating reagents, low atom economy and multi-step operation of starting materials.…”
mentioning
confidence: 99%